Chapter 2: The rise of big food and agriculture: corporate influence in the food system - Clapp, Jennifer (Edward Elgar Publishing, 2022)
Corporate concentration has become a dominant feature of the modern industrial food system in recent decades. In nearly all stages of global food supply chains, from farm inputs, to production, to trade, to processing and food retail, a common pattern is that just a handful of firms tend to dominate. This chapter examines the key drivers of this trend as well as its wider implications. It shows that a combination of financial incentives, technological change, and shifts in the broader regulatory context have been important factors in the trend toward increased concentration in the sector in recent decades. It also outlines how concentration has lent enormous power to the firms at the top to shape the parameters of markets as well as the broader policy and regulatory context to serve their own interests. These dynamics have important implications for broader food system goals such as equity, participation, sustainability, and choice.